Effects of situational variables and starting aqarter score in the outcome of elite women's water polo game quarters - Gómez, M.-Á.; DelaSerna, A.; Lupo, C.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2014)
The present study aimed to identify the interactive effects of Starting Quarter Score and Game Location according to Quality of Opposition in final quarters score in elite women's water polo. Data comprised 1,828 quarters from 457 close games (goal-difference of less than 4 goals) from the Spanish water polo women's First division (2010-2011 and 2011-2012 seasons). The interactive effects of situational variables on Starting Quarter Score according to the quality of opposition (three game contexts: HIGH vs. HIGH; HIGH vs. LOW; LOW vs. LOW) during close games were analyzed using linear regression analysis. Results showed that Starting Quarter Score reported significant effects in all the Quality of Opposition game contexts for all game quarters, and second, third, and fourth quarter. Conversely, game location showed that playing away increased by 0.68 goals in the second quarter of HIGH vs. HIGH games, and increased by 0.81 goals in the fourth quarter of LOW vs. LOW games, with respect to counterparts. Therefore, Quality of Opposition, Game Location, and Starting Quarter Score have important effects on women's water polo game dynamics especially during the first half of close games. Finally, this study provides useful references for coaches' plans (i.e., effective strategic approach/training proposals) to improve their women players' performance.